2014
DOI: 10.4184/asj.2014.8.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Vertebroplasty and Kyphoplasty for Osteoporotic Vertebral Compression Fractures

Abstract: Study DesignA retrospective study.PurposeThe aim of this study is to compare the efficacy and outcome of vertebroplasty compared with unipedicular and bipedicular kyphoplasty for the treatment of osteoporotic vertebral compression fractures in terms of pain, functional capacity and height restoration rates.Overview of LiteratureThe vertebroplasty procedure was first performed in 1984 for the treatment of a hemangioma at the C2 vertebra. Kyphoplasty was first performed in 1998 and includes vertebral height rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…An increasing number of studies have been conducted to apply unilateral balloon kyphoplasty in the treatment of OVCFs (13)(14)(15)(16)(17)(18)(19). Scholars have compared the clinical and radiological results of unilateral and bilateral kyphoplasty approach (20)(21)(22)(23)(24)(25)(26)(27)(28). However, the efficacy and safety of unilateral kyphoplasty, or whether a unilateral or a bilateral approach is superior, have been controversial.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have been conducted to apply unilateral balloon kyphoplasty in the treatment of OVCFs (13)(14)(15)(16)(17)(18)(19). Scholars have compared the clinical and radiological results of unilateral and bilateral kyphoplasty approach (20)(21)(22)(23)(24)(25)(26)(27)(28). However, the efficacy and safety of unilateral kyphoplasty, or whether a unilateral or a bilateral approach is superior, have been controversial.…”
Section: Meta-analysismentioning
confidence: 99%
“…Nine studies reported a total of 451 patients in the unilateral kyphoplasty group and 418 in the bilateral kyphoplasty group (20)(21)(22)(23)(24)(25)(26)(27)(28). The clinical data of included studies was presented in Table 3.…”
Section: Comparison Of Unilateral and Bilateral Percutaneous Kyphoplastymentioning
confidence: 99%
“…On the other hand, BKP helps in long term pain relief, restoration of vertebral height and decreased incidence of cement leakage. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Conclusion:-PVP and BKP both are effective in vertebral augmentation and pain-relief in patients with osteoporotic or tumorassociated VCFs in short and long term management. PVP and BKP both give immediate pain relief and improvement in physical function.…”
Section: Complication:-mentioning
confidence: 99%
“…At present, minimally invasive surgery has become an important treatment for spinal metastases (3). Percutaneous vertebroplasty (PVP), as an important means of minimally invasive surgery, has been widely used in vertebral compression fractures caused by osteoporosis, vertebral hemangioma, multiple myeloma and vertebral metastases (4,5). Bone cement leakage is the most common complication of PVP, with an incidence of 22% to 82% (6).…”
Section: Introductionmentioning
confidence: 99%